Psychosexual morbidity in women with ovarian cancer. Issue 12 (28th October 2020) - Logue, Chloe Alice; Pugh, Julia; Jayson, Gordon
Abstract : Increasing numbers of women are surviving for longer with epithelial ovarian cancer. Consequently, there is increased focus on long-term quality of life in national guidance. Psychosexual morbidity including vaginal dryness, pain during intercourse (dyspareunia), reduced libido, and negative perceived body image exacerbate stress and anxiety and impact intimate relationships. Although a priority for women with epithelial ovarian cancer, clinicians seldom discuss sexual problems. Therefore, psychosexual morbidity and the associated distress remain unaddressed. We synthesize evidence from primary qualitative and quantitative research studies exploring psychosexual morbidity in women with epithelial ovarian cancer to identify potential risk factors and common symptoms, to facilitate the identification and management of sexual problems in clinic. Literature (2008–19) from 10 databases identified 29 suitable publications (4116 patients). The papers were assessed to answer the question: "What are the key potential risk factors and presentations of psychosexual morbidity in women with epithelial ovarian cancer?" Current literature lacks consensus in defining clinically significant psychosexual morbidity in women with epithelial ovarian cancer. Discrepancies in measurement tools, questionnaires, and primary outcome measures confound result interpretation, limiting wider application. Key potential risk factors identified included: younger age (<53 years); pre-menopausal status at diagnosis; aim of treatment; extent of surgery; more courses of chemotherapy; cardiovascular co-morbidities; and anxiety and depression. Up to 75% of women with epithelial ovarian cancer reported adverse changes in their sex lives following diagnosis and, of the sexually active, vaginal dryness affected 81–87% and pain 77%. Other prevalent symptoms included: reduced sexual desire and activity, impaired orgasm, diminished perceived body image, and reduced partner intimacy. Psychosexual morbidity represents a significant unmet need for women with epithelial ovarian cancer. Effective treatment necessitates a multimodal approach encompassing medical, psychoeducational, and physiotherapy-based strategies. Future studies need agreement in their questionnaires, definitions, thresholds, and primary outcome measures for meaningful interstudy comparisons to be drawn.